The Phenomenon That Influenced The Development of Cool Japan in Indonesia - Fitri Alfarisy; Aditya Prayoga; Ayu Alfi Syahrina; Nadya Salma Salsabila (International Journal Labs, 2021)
As it is well known that Japan has many unique cultures that can attract people from other countries. Since the mid-1960s, Japanese culture, especially popular culture, has continued to develop to this day. The peak of its development was in 2002, when an article written by Douglas McGray entitled